Prevalence of haemosporidian parasites in raptors in rehabilitation centers across the United States - Laura A. Kwasnoski; Ishika Sharma; Dominic Carrea; Neha Larson; Michael D. Collins; Vincenzo A. Ellis (Journal of Ornithology, 2026)
Avian haemosporidians are common vector-transmitted parasites that infect birds. Although avian haemosporidians have been studied extensively in songbirds, less is known about haemosporidian prevalence in raptors, particularly in the United States. We used molecular methods to test blood samples collected from raptors at five wildlife rehabilitation centers across the United States for avian haemosporidians. We identified parasites from the genera Haemoproteus , Leucocytozoon , and Plasmodium using a multiplex PCR and determined prevalence by raptor host species and site. Almost half of the raptors tested (47%) were infected with at least one parasite, with Plasmodium detected at the highest frequency (28%) followed by Haemoproteus (21%), and Leucocytozoon (12%). Prevalence of each parasite genus varied among host species. For example, Haemoproteus prevalence was higher in American Kestrels ( Falco sparverius ; 55%), Barred Owls ( Strix varia ; 58.2%), and Great-Horned Owls ( Bubo virginianus ; 43.8%) than in Bald Eagles ( Haliaeetus leucocephalus ; 0%) or Black Vultures ( Coragyps atratus ; 0%) . Prevalence also varied among sites for all three parasite genera. However, we did not detect a species by site interaction effect for prevalence, suggesting that relative rates of parasite infection among raptor species are relatively constant across the region we investigated. This work adds to our understanding of raptor disease ecology at a regional geographic scale. Future analyses will focus on the diversity and distribution of parasite genetic lineages among these host species and sites.